Si precursor inhibitors for area selective deposition of Ru - Gu, Bonwook; Yasmeen, Sumaira; Oh, Geun Ha; Oh, Il Kwon; Kang, Youngho; Lee, Han Bo Ram (Applied Surface Science, 2024)
Area-selective atomic layer deposition (AS-ALD) using highly process-compatible precursor inhibitors (PIs) has garnered attention because of the need to overcome three-dimensional nanofabrication bottlenecks. The main advantages of precursor inhibitor (PI) molecules are their high process compatibility and their inherent bifunctionality as inhibitors and precursors. Herein, we examined the inhibition properties, adsorption mechanisms, and adsorption configurations of two PIs, bis(N,N-dimethylamino)dimethylsilane (PI1) and tris(dimethylamino)silane (PI2). Both PIs selectively inhibited the SiO2 surface but not the Cu surface, which enabled the AS-ALD of Ru films on the latter. The inhibition mechanisms were elucidated on the basis of chemical reactivity and steric hindrance considerations using density functional theory calculations and Monte Carlo simulations. PI1 featured a larger areal coverage than PI2 because of the favorable adsorption configuration of the former, inducing a stronger steric hindrance effect and achieving a higher inhibition performance against Ru ALD, although the two PIs had similar chemical reactivities toward the examined surface. Furthermore, PI1 and PI2 formed SiO2 ALD films when ozone was used as a reactant. The differences in the growth characteristics of the corresponding ALD SiO2 films were explained by the different adsorption configurations of PIs. Thus, our work elucidates the adsorption configurations of silane-based PIs and thus paves the way for the more effective utilization of their bifunctionality, inhibition properties, and growth characteristics in future AS-ALD processes.
Keywords: Area selective; Area-selective deposition; Atomic-layer deposition; Density functional theory; Density-functional-theory; Inhibition property; Monte Carlo's simulation; NanoPatterning; Selective deposition; Thin-films; Area-selective deposition; Atomic layer deposition; Density functional theory (DFT); Monte Carlo (MC) simulations; Nanopatterning; Thin film